1991
DOI: 10.1177/073401689101600204
|View full text |Cite
|
Sign up to set email alerts
|

Policing Domestic Violence: Perceptions, Experience, and Reality

Abstract: This research explores police attitudes and experiences with a departmental policy favoring arrest in cases of domestic violence. It also addresses the impact that such a policy may have on future domestic violence calls. Analyses were based on two data sets: (a) calls and arrests recorded for two years prior to the implementation of an arrest policy and for two years after and (b) a survey of patrol and command officers. This is a study of the impact of an arrest policy on the police; it is not a study of dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 11 publications
1
28
0
Order By: Relevance
“…Research considering the potential influence of race, immigrant status, age, and=or income=class shows mixed findings. Some research suggests that police response (e.g., arrest) to IPV is similar regardless of a woman's background characteristics (Fleury 2002;Friday, Metzgar, and Walters 1991), whereas other studies have shown differential police response to IPV (Bowker 1982;Robinson and Chandek 2000;Russell and Light 2006;Yegidis and Berman Renzy 1994), highlighting the impact of women's sociodemographics on their likelihood of obtaining much needed support.…”
Section: Response From and Satisfaction With The Policementioning
confidence: 96%
“…Research considering the potential influence of race, immigrant status, age, and=or income=class shows mixed findings. Some research suggests that police response (e.g., arrest) to IPV is similar regardless of a woman's background characteristics (Fleury 2002;Friday, Metzgar, and Walters 1991), whereas other studies have shown differential police response to IPV (Bowker 1982;Robinson and Chandek 2000;Russell and Light 2006;Yegidis and Berman Renzy 1994), highlighting the impact of women's sociodemographics on their likelihood of obtaining much needed support.…”
Section: Response From and Satisfaction With The Policementioning
confidence: 96%
“…For example, a large body of research considered whether police officers are more likely to be injured in domestic violence cases (Friday, Metzger, & Walters, 1991;Skorackyj, 1994;Stalnaker, Shields, & Bell, 1993). Research also suggested that some criminal justice officials have problems developing a rapport with domestic violence victims (Websdale, 1995;Websdale & Johnson, 1997).…”
Section: Discussionmentioning
confidence: 98%
“…Threats against the officer and use/presence of weapons have been found to increase the likelihood of an arrest (Avakame and Fyfe 2001). Conversely, lack of cooperation by the victim has been observed to lower the chances of an arrest (Friday et al 1991). The relationship between the victim and offender has been found to affect the arrest decision, while the presence of children has been observed to have mixed effects (Robinson and Chandek 2000).…”
Section: Literature Reviewmentioning
confidence: 94%
“…Research among urban and suburban officers reveals that both the infliction and seriousness of injury to the victim influence arrest decisions, especially those indicating a serious physical assault had taken place (Avakame and Fyfe 2001;Finn and Stalans 1995;Hall 2005;Mignon and Holmes 1995). Furthermore, the demeanor of the suspect is important in the arrest decision, with an arrest being more likely when the suspect's demeanor with the officer(s) is poor or combative (Friday et al 1991;Waaland and Keeley 1985). Additionally, when the suspect appears to be under the influence of drugs or alcohol, there is a greater likelihood of arrest (Avakame and Fyfe 2001;Mignon and Holmes 1995).…”
Section: Literature Reviewmentioning
confidence: 96%